2022
DOI: 10.3389/fimmu.2022.894789
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PCSK9 Ameliorates Graft Vascular Disease in Mice by Inhibiting NLRP3 Inflammasome Activation in Vascular Smooth Muscle Cells

Abstract: BackgroundGraft vascular disease (GVD), which limits the long-term survival of patients after solid-organ transplantation, is associated with both immune responses and nonimmune factors, including dyslipidemia. Recent studies have shown that inhibition of proprotein convertase subtilisin/kexin type 9 (PCSK9), a U.S. Federal Drug Administration-approved treatment for hyperlipidemia, reduces cardiovascular events, regulates inflammatory responses, and enhances the efficacy of immune checkpoint therapy in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
3
13
0
Order By: Relevance
“…With these concepts in mind, before characterizing the content of EVs, we first noted that PCSK9 favoured a phenotypic switch of human VSMCs towards a synthetic phenotype. This evidence is in line with previous observations reporting that PCSK9 induces cell proliferation in mouse- or rat-derived smooth muscles [ 30 , 35 ]. However, it must be acknowledged that one study, by using both human aortic VSMCs and mouse VSMCs knockout of Pcsk9 , demonstrated the opposite, namely, PCSK9 inhibits proliferation and induces polyploidization, senescence and apoptosis [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With these concepts in mind, before characterizing the content of EVs, we first noted that PCSK9 favoured a phenotypic switch of human VSMCs towards a synthetic phenotype. This evidence is in line with previous observations reporting that PCSK9 induces cell proliferation in mouse- or rat-derived smooth muscles [ 30 , 35 ]. However, it must be acknowledged that one study, by using both human aortic VSMCs and mouse VSMCs knockout of Pcsk9 , demonstrated the opposite, namely, PCSK9 inhibits proliferation and induces polyploidization, senescence and apoptosis [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…By influencing the content of EVs released from VSMCs, PCSK9 favours a pro-inflammatory phenotype in in vitro models of endothelial cells, monocytes and macrophages as well as in zebrafish embryos. Considering that VSMCs play critical roles in multiple vascular diseases, including atherosclerosis [ 27 ], the rationale of using VSMCs as a proxy is based on the following assumptions: VSMCs express significant levels of PCSK9 [ 18 , 28 ] which are able to downregulate the expression of LDLR expression in macrophages [ 15 ] and monocytes [ 29 ]; a raised expression of PCSK9 is found in VSMCs under pro-inflammatory stimuli [ 29 ] and in regions at low shear stress (3–6 dyn/cm 2 ) [ 16 ]; VSMCs isolated from Pcsk9 −/− mice, compared to those of Pcsk9 +/+ mice, have a reduced proliferation rate and a suppressed migratory capacity [ 17 , 30 ]; PCSK9 mediates a switch towards a pro-calcific phenotype of VSMCs [ 5 ]; there is an increased number of the synthetic phenotype of VSMCs that express PCSK9 in acute aortic dissection samples [ 31 ]; in a synthetic or proliferative non-contractile state, VSMCs exhibit an increased production of EVs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the PCSK9 protein has been reported as the main cause of degradation of LDLRs in HepG2 cells and the 3GCW target structure was identified [40] . In addition, one of the reasons for the selection of the target structure of PDB ID: 3GCW (PCSK9 protein) is that the PCSK9 protein plays a significant role in controlling TGFβ‐R1 degradation and expression [69–71] . Finally, the target protein for the A549 lung cancer cells was identified as PDB ID: 1M17, the crystal structure of the epidermal growth factor receptor tyrosine kinase (EGFR‐K) domain [39] .…”
Section: Resultsmentioning
confidence: 99%
“…Under hypoxic conditions, PCSK9 promotes the secretion of proinflammatory cytokines by macrophages to exacerbate hypoxia/ reoxygenation-induced cardiomyocyte injury by activating the NF-kB signaling pathway (91). Moreover, PCSK9 knockout significantly inhibits hypoxia-induced inflammation and cell death, inhibits macrophage recruitment, and suppresses the migration and proliferation of VSMCs; these effects are related to the inhibition of NLRP3 inflammasome activation (15). Using sepsis models in HUVECs and mice, Huang et al found that increased PCSK9 expression during sepsis activates the TLR4/MyD88/NF-kB and NLRP3 pathways to induce inflammation, which results in vascular endothelial dysfunction and decreased survival (14).…”
Section: Effects Of Pcsk9 On the Nlrp3 Inflammasome Signaling Pathwaymentioning
confidence: 99%
“…Recently, several studies have reported that PCSK9 activates the NLRP3 inflammasome signaling pathway and the associated inflammation (13)(14)(15). Conversely, the NLRP3 inflammasome signaling pathway can regulate PCSK9 secretion (16).…”
Section: Introductionmentioning
confidence: 99%